PENANAMAN BUDI PEKERTI DALAM TINDAK TUTUR GURU SEBAGAI DASAR PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Heri Suwignyo (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2011)
Abstract: This study aims to describe and explain education of  character intelligence of learner in speech acts among (governence) substance. The use of the among substance in the speech act in teaching is a natural phenomenon in the context of the classroom. In effort to explain the phenomena, the research used a naturalistic qualitative research with pragmatic design. Based on data analysis there were three groups research results, ie. ineducationg learners' character intelligence, aspects of intellectual, emotional, conational embodied in cipta (creating), rasa (sensing), karsa (initiating) speech acts.   Abstrak: Penelitian ini bertujuan mendeskripsikan dan menjelaskan penanaman kecerdasan budi pekerti siswa dalam tindak tutur substansi among. Penggunaan tindak tutur substansi among dalam pembelajaran merupakan fenomena alamiah dalam konteks kelas. Untuk menjelaskan itu, digunakan penelitian kualitatif naturalistik dengan ancangan pragmatik. Berdasarkan analisis data diperoleh tiga kelompok temuan penelitian  bahwa dalam penanaman kecerdasan budi pekerti siswa aspek intelektual, emosional, dan konasional diwujudkan  dalam tindak tutur cipta, rasa, dan karsa.